Injury prevention program for juvenile soccer players: Effects on physical performance, awareness of injury prevention measures and injury rates / Ahmed Fadhil Farhan - Farhan, Ahmed Fadhil (Institute of Graduate Studies, UiTM, 2016)
The purpose of this study was to investigate the effects of an injury prevention program (IPP) on physical performance, awareness of injury prevention measures and incidence of injury among junior male Malaysian soccer players. Participants (N=50, age=13.34±0.47 years, BMI=20.96±1.57 kg/m2) were assigned randomly into experimental (EXP, n=25) or control (CON, n=25) groups. The IPP consisted of exercise training (five times per week) and educational classes (three times per week) for 12 weeks. The CON group continued training as usual. Both groups performed a battery of soccer-specific physical tests at baseline, middle and after the intervention; 1) Standing long jump test (explosive leg power); 2) Sargent jump test (vertical jump height); 3) Illinois agility test (agility); 4) Prone hold test (core stability) and 5) 20m sprint test (running speed). A questionnaire containing 24 questions regarding awareness of injury prevention strategies and practices, as well as a measure of injury rates was administered at baseline and post-intervention. The incidence of injury was calculated using a formula: (incidence rate = number of injuries/ hours of exposure) × 1000…